2020
DOI: 10.1104/pp.20.00906
|View full text |Cite
|
Sign up to set email alerts
|

Redox Modification of the Iron-Sulfur Glutaredoxin GRXS17 Activates Holdase Activity and Protects Plants from Heat Stress

Abstract: A cysteine-dependent redox modification of the iron-sulfur cluster glutaredoxin GRXS17 activates its holdase activity and protects plants from heat stress AUTHOR CONTRIBUTION

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 75 publications
1
31
0
Order By: Relevance
“…Though HSPs might be interacting target proteins of GRXs, how AtGRXS17 interacts with HSPs is unknown. In the recent study, GRXS17 is found to possess both foldase and redox-dependent holdase activity which are further supporting the role of GRXS17 as a molecular chaperone [ 70 ].…”
Section: Discussionmentioning
confidence: 74%
“…Though HSPs might be interacting target proteins of GRXs, how AtGRXS17 interacts with HSPs is unknown. In the recent study, GRXS17 is found to possess both foldase and redox-dependent holdase activity which are further supporting the role of GRXS17 as a molecular chaperone [ 70 ].…”
Section: Discussionmentioning
confidence: 74%
“…The chaperone activity of APX is not an isolated example for an antioxidant enzyme. Upon destabilization of the iron-sulfur cluster in a redox-and temperature-dependent manner, GRXS17 becomes a holdase whose activity probably protects the root meristem under high temperatures (Martins et al, 2020), and possibly could be linked also to its rerouting to the nucleus, because a GFP-GRXS17 fusion protein resides in the nucleus during heat stress (Wu et al, 2012). Moreover, overexpression of AtGRXS17 in tomato improved heat stress resilience together with improved redox homeostasis and elevated HSP expression (Wu et al, 2012).…”
Section: Beating the Heat: Keeping The Antioxidant Machinery At Speedmentioning
confidence: 99%
“…However, an impaired thermotolerance of the grxS17 was previously reported (Cheng et al, 2011) (Knuesting et al, 2015) (Martins et al, 2020a). While at 27°C, the grxS17 mutation was suggested to impair auxin signaling (Cheng et al, 2011), the 35°C treatment was also suggested to induce holdase activities of GRXS17 (Martins et al, 2020a). Whether a lower glutathione level would limit GRXS17 thermotolerance activities should be further investigated.…”
Section: Discussionmentioning
confidence: 93%
“…This might be due to redundancy between members of the large glutaredoxins family (Riondet et al, 2012). However, an impaired thermotolerance of the grxS17 was previously reported (Cheng et al, 2011;Knuesting et al, 2015;Martins et al, 2020a). While at 27°C, the grxS17 mutation was suggested to impair auxin signaling (Cheng et al, 2011), the 35°C treatment was also suggested to induce holdase activities of GRXS17 (Martins et al, 2020a).…”
Section: Discussionmentioning
confidence: 95%